Examining the Effects of Diet Composition, Soluble Fiber, and Species on Total Fecal Excretion of Bile Acids: A Meta-Analysis - Pezzali, Julia Guazzelli; Shoveller, Anna K.; Ellis, Jennifer (Frontiers in Veterinary Science, 2021)
Bile acids (BA) are produced in the liver and conjugated with glycine or taurine before being released into the small intestine to aid with lipid digestion. However, excessive BA losses through feces can occur due to several dietary factors that in turn require greater production of BA by the liver due to a reduction in BA recycling. Consequently, net utilization of taurine and/or glycine is increased. To quantify this impact, we conducted a meta-analysis to investigate the effect of soluble fiber, diet composition, and species on fecal excretion of BA. After a systematic review of the literature, twelve studies met all inclusion criteria. Dietary carbohydrate, protein, fat, cellulose, cholesterol, soluble fiber and animal species were tested as independent variables. Mixed models were developed treating study as a random effect, and fixed effect variables were retained at P<0.05 significance and where collinearity was absent between multiple X variables. A total of ten studies comprised of four species ((rat=5), hamster (n=1), guinea pig (n=3) and dog (n=1)), and 30 observations were evaluated in the final models after outlier removal. Model evaluation was based on the corrected Akaike Information Criteria, the concordance correlation coefficient and the root mean square prediction error. Three base models were developed, examining carbohydrate, protein and fat impacts separately. The best fitting models included the fixed effect of species and the interaction between soluble fiber (yes/no) and dietary carbohydrate, protein or fat (%, as-fed). Increased concentrations of dietary protein and fat resulted in greater fecal excretion of BA (P<0.05). Conversely, increasing levels of dietary carbohydrate led to lower excretions of BA (P<0.05). Increased dietary soluble fiber containing ingredients resulted in greater excretion of BA in all models (P<0.05). Rats had greater excretion of BA compared to hamsters and guinea pigs (P<0.05) in all models, and also compared to dogs (P<0.05) in the carbohydrate model. The findings from this meta-analysis indicate that not only soluble fiber, but also increasing levels of dietary fat and protein may result in greater fecal excretion of BA, potentially altering taurine and/or glycine metabolism and affecting the need for diet delivery of these AA.